Optimization of Production Inputs For Potato Farming In Sumber Brantas Village, Bumiaji District, Batu City - Lilis Syarifatul Karima; Dyah Erni Widyastuti; Gumoyo Mumpuningsih; Abdul Wahib Muhaimin; Riyanti Isaskar (Pelopor Publikasi Akademika, 2024)
Potatoes are a vital horticultural commodity in Indonesia, serving as an alternative staple food and an industrial raw material. However, potato farming in Sumber Brantas Village, Bumiaji District, Batu City faces inefficiencies due to excessive use of inputs, such as seeds and fertilizers, and financial constraints arising from rising input costs. This study aims to evaluate the efficiency and optimization of production inputs in potato farming to enhance productivity and sustainability. A quantitative research approach was employed, with data collected from 50 potato farmers through interviews and questionnaires. The Cobb-Douglas production function was used to analyze input efficiency, supported by classical assumption tests, including multicollinearity, heteroscedasticity, and normality tests. The findings reveal that land area and seeds are relatively efficient inputs, while fertilizers, pesticides, and labor remain inefficient and underutilized. Further optimization analysis showed that none of the production inputs had achieved optimal levels, indicating overuse in some cases and underutilization in others. These inefficiencies significantly limit production outcomes. The study concludes that targeted interventions are required to optimize resource allocation and improve input management. These insights provide valuable recommendations for farmers and policymakers to enhance agricultural productivity and economic viability in the region, contributing to more sustainable potato farming practices.